Beyond Linguistics: A Humanistic Approach to Language Teaching - Casambre, Nelia G. (The Archive; 1983: Trends in Philippine Linguistics: Papers of the First Philippine Linguistics Congress, 2025)
For the last three decades, much of the practical considerations in language learning as well as language instruction were based on the mechanistic and distributional analyses of linguistics. Language behavior was no more than a structurally patterned behavior that could be acquired through a habit-formation process. Language learning was thus to many a somewhat dull process of meaningless repetitions and rote memorization. This was the audiolingual or structural approach, an approach based on the assumption that the learner could be conditioned to learn a language by going through a hierarchical structuring of language learning activities leading toward the acquisition of a new set of language habits.